Artisans, Objects and Everyday Life in Renaissance Italy : The Material Culture of the Middling Class - Hohti, Paula, 1968- (Book collections on Project MUSE., 2020)
Did ordinary Italians have a 'Renaissance'? This book presents the first in-depth exploration of how artisans and small local traders experienced the material and cultural Renaissance. Drawing on a rich blend of sixteenth century visual and archival evidence, it examines how individuals and families at artisanal levels (such as shoemakers, barbers, bakers and innkeepers) lived and worked, managed their household economies and consumption, socialised in their homes, and engaged with the arts and the markets for luxury goods. It demonstrates that although the economic and social status of local craftsmen and traders was relatively low, their material possessions show how these men and women who rarely make it into the history books were fully engaged with contemporary culture, cultural customs and the urban way of life.--